Exploring peer review as a pedagogical tool to enhance paragraph-writing skills in university students - Putra, Aidil Syah; Rohim, Abdul; Zanzali, Noor Azlan Ahmad (JEES (Journal of English Educators Society), 2025)
This study explores the role of structured peer review as a pedagogical tool to enhance paragraph-level writing skills among university students in Indonesia. Academic writing remains one of the most demanding competencies for learners, particularly in producing cohesive and coherent paragraphs. In contexts where large classes and limited teacher feedback constrain the learning process, peer review offers a collaborative approach that distributes responsibility for feedback while fostering deeper engagement with writing. Employing a qualitative case study design, this research involved 25 fourth-year students in an English composition course. Data were gathered from multiple sources, including students’ writing drafts collected across several peer review cycles, classroom observations, surveys, and semi-structured interviews. This triangulated approach allowed for a rich exploration of how students’ paragraph writing developed over time and how they perceived the peer review process. The findings indicate that students demonstrated notable progress in crafting clearer topic sentences, elaborating supporting details, and producing more consistent concluding sentences. Beyond textual improvements, students reported increased confidence, greater accountability toward peers, and stronger reflective habits. These gains were facilitated by scaffolding strategies such as rubrics, checklists, and teacher modeling, which guided students to provide feedback that moved beyond surface-level corrections toward higher-order concerns of coherence and unity. The study concludes that structured peer review supports not only the improvement of writing products but also the cultivation of collaborative and self-regulated learning practices. As such, it underscores the potential of peer review to be integrated as a core component of English as a Foreign Language (EFL) writing instruction in higher education.